ABUSE OF AUTHORITY OFFENSE THEOLOGICAL RECONSTRUCTION LAW ERADICATION OF CORRUPTION (LAW NUMBER 31 OF 1999 JO. LAW NUMBER 20 OF 2001) BASED ON VALUE OF JUSTICE - As'adi M. Al-ma'ruf; Gunarto Gunarto; Sri Endah Wahyuningsih (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
Tort has been established in Article 2, was misuse of authority by Article 3 of the Law on Corruption Eradication. Abuse of authority but also an act against the law, then Article 2 are also applicable in the case of the offense of abuse of authority. In practice at the Corruption Court, normally the public prosecutor filed a defendant to trial on charges subsidaritas, the primary charge Article 2 and Article 3 of the subsidiary charge. Most judges decide the primary charge is proven, and some other judges decide the primary charges not proven and proven subsidiary charges. Objective: to analyze the weaknesses of the offense of abuse of authority, and the subsequent reconstruction of the formulation of the offense of abuse of authority, based on the values of justice. Method : This is the paradigm of constructivism and sociological juridical approach, the analytical descriptive nature. Sources of primary data with field study to the Jakarta High Court Corruption, and secondary data in the form of decisions offense penyaahgunaan authority and literature in the form of legislation and literature books. The collected data were analyzed descriptively qualitative. Result : There are weaknesses in the formulation of Article 3, giving rise to discrimination against the accused. Therefore be reconstructed based on the values of justice, to redraft Article 3 to a penalty equal to Article 2, plus one paragraph to a penalty under minimal. Keywords: Reconstruction, Abuse of Power, Corruption, value of justice.